Deteriorating Habitats and Conservation Strategies to Repopulate the Endangered Indus River Dolphin (Platanista gangetica minor); a Lesson Learned From the Conservation Practices of the Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Nabi, Ghulam; Ahmad, Shahid; McLaughlin, Richard William; Hao, Yujiang; Khan, Suliman; Ahmad, Naveed; Ahmad, Saeed; Kiani, Muhammad Shoaib; Wu, Yuefeng; Li, Dongming (Frontiers in Marine Science, 2021)
The Indus River dolphin (IRD; Platanista gangetica minor) is an endangered and blind freshwater cetacean, endemic to the Indus River system of Pakistan and India. This review article provides detailed information about the major challenges IRDs are facing, and their possible consequences on the population dynamics of the IRD. Furthermore, we have suggested future conservation strategies for the IRD based on the lesson learned from the conservation of the Yangtze finless porpoise (YFP; Neophocaena asiaeorientalis), a Critically Endangered freshwater cetacean. The major challenges for IRDs are habitat degradation, habitat fragmentation, and several types of industrial and agricultural pollutants. Worsening climatic changes, illegal fishing, and overfishing are additional threats. The construction of several barrages has fragmented the population into several short segments, some of which are too small for the IRDs to survive. In some segments, the population status of the IRD is unknown. In the remaining populations, genetic inbreeding, water shortage, canal entrapment, and altered ecological environment are potent negative factors for the survival of the IRD. Conservation strategies including fishing bans, translocation, and future research (tagging, periodic health assessments, necropsy and virtopsy, understanding the reproductive biology, and genomics) are possible recommendations. Very serious conservation efforts are needed to save the IRD from decline keeping in view the water shortage, pollution, lack of health assessment studies, and habitat degradation and fragmentation.